Poetic Purposes in Muhammad Muhammad Ali’s Poetry: A Descriptive, Critical and Analytical Study - Abdulrahman Ahmed, Jamaluddin Ibrahim; Suleiman Bakht, Adam Abdul Shafie; Ibrahim Mohamed, Ibrahim Abdullah; Al-Amin Ahmed, Mohamed Ahmed (Journal of Tikrit University for Humanities, 2025)
This study aims at knowing the poetry purposes in the poets of Mohammed Mohammed Ali. It presents some samples of his poetry in asceticism , description, pride, lamentation, praise, satire, flirtation and the national poems. The research consist of three sections as follows: section one examines asceticism, description and pride. Section two discusses praise and satire. Section three deals with lamentation and flirtation. The research adopts the descriptive analytical method in discussing the poetic texts, explanation, analysis and revealing their attractions .